Speed Control of DC Motor using Four-Quadrant Rectifier based on Internet of Things - Gozi, Muhammad; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2025)
DC motor is one of the important components in various industrial and automation applications due to its ability to provide precise speed control. This research aims to design and implement a DC motor speed control system using a four-quadrant rectifier based on the Internet of Things (IoT). This system allows the DC motor to operate in four quadrants, namely forward motor, reverse motor, forward regenerative, and reverse regenerative, thus providing flexibility and efficiency in controlling speed and rotation direction. By utilizing IoT technology, motor control can be done wirelessly through web-based applications or mobile devices, enabling real-time remote monitoring and control. The test results show that the system is able to accurately control the speed of a DC motor according to a given reference value, and can adapt to changes in load. The use of this IoT-based four-quadrant rectifier is expected to improve energy efficiency, operational flexibility, and ease of integration in modern automation systems.